Evaluation of Coal Transport Route in Jambi City (Talang Duku Port-East Ring Road II) - Angella, Dwi; Soehodho, Sutanto; Nahry, Nahry (UI Scholars Hub, 2024)
In its implementation, the role of coal transportation infrastructure is important in supporting the mining industry in Jambi City. However, it also causes various complex problems; one of them is traffic congestion on arterial roads in Jambi City. In May 2023, the Jambi Regional Police of the Republic of Indonesia issued a notification letter to stop the mobilization of coal transportation in Jambi Province. The policy caused several coal companies to switch their transportation method to shipping in order to continue operating, while several other companies stopped operating until an indeterminate time. Therefore, this study aims to compare traffic performance before and after the implementation of the policy on Jambi City arterial roads, especially on Talang Duku Port Road and East Ring Road II. The method used was a comparative analysis of the degree of saturation before and after the enactment of regulations on the prohibition of coal truck operations. The results of this study show the importance of traffic management as one of the solutions to reduce traffic congestion. Nevertheless, other alternatives are still needed to support the smooth operation of coal transportation activities.